HYPOTONIC MACULOPATHY AFTER TRABECULECTOMY WITH POSTOPERATIVE USE OF 5-FLUOROURACIL - (:unkn) unknown (KARGER, 1994)
We evaluated two patients who developed hypotonic maculopathy following trabeculectomy and adjunctive 5-fluorouracil injections. Both patients had ocular hypotony and decreased visual acuity following these injections. The first case showed marked choroidal foldings, retinal striae, increased retinal vascular tortuosity, engorgement and optic disc oedema. The second case had radial perifoveal retinal striae, increased retinal vascular tortuosity and engorgement. The first patient regained pre-operative visual acuity while the second case had a visual acuity of 20/25 without any intervention. Fundus changes were less marked 12 months after initial evaluation in both cases. Hypotonic maculopathy is a reversible complication of trabeculectomies with adjunctive use of 5-fluorouracil.
Keywords: 5-FLUOROURACIL; HYPOTONY; MACULOPATHY; TRABECULECTOMY; GLAUCOMA